RESPONSE OF SWEET CORN (ZEA MAYS L. VAR. MACHO F1 ) AS AFFECTED BY RICE STRAW MULCH AND LEVELS OF NITROGEN FERTILIZER - Escototo, Angela R; Limbason, Mary Ann I; Cobico, John Albert; Cagasan, Ulysses A (Journal of Agriculture and Technology Management, 2023)
Nitrogen is an essential micronutrient that influences the growth and yield of sweet corn. However, it has many avenues of losses like volatilization and soil moisture thus, it must be maintained though mulching. The mulch material protects soil surface from sunlight which reduces evaporation by preserving soil water and altering soil temperature. This study was conducted to evaluate the effect of rice straw mulch and Nitrogen level, and assess the profitability of sweet corn production. The treatments designated as follows: T 1 - 0-60-60 kg ha -1 N, P 2 O 5 , K 2 O, T 2 - 60-60-60 kg ha -1 N, P 2 O 5 , K 2 O, T 3 - 90-60-60 kg ha -1 N, P 2 O 5 , K 2 O, T 4 - 120-60-60 kg ha -1 N, P 2 O 5 , K 2 O, and T 5 - 150-60-60 kg ha -1 N, P 2 O 5 , K 2 O. The experimental area was laid out in a Randomized Complete Block Design (RCBD) with three replications. Results revealed that sweet corn applied with different levels of Nitrogen mulched with rice straw significantly affected the number of days from sowing to silking, stover yield, number of marketable ears plot -1 , weight (t ha -1 ) of marketable ears, ear diameter, and total ear yield (t ha -1 ). Application of 120-150 kg of N ha -1 resulted in late silking comparable to sweet corn without N. Application of N regardless of rates increased the stover yield, ear diameter, and total ear yield (t ha -1 ). Application of 150 kg of N ha -1 gave the highest weight of marketable yield. Thus, sweetcorn requires higher rates of nitrogen fertilizer to obtain its optimum ear yield tha -1 .